Enhancing VIX Shock Prediction via a Probabilistic Attention Transformer - Kim, Jin Su; Lee, Zoonky (Bright Publisher, 2025)
This study proposes a Probabilistic-Attention Transformer for forecasting abrupt shifts in the Volatility Index (VIX), advancing volatility modeling by directly embedding externally estimated shock probabilities into the attention mechanism. The core idea is to modify similarity-based attention scores with daily shock probabilities derived from stochastic diffusion equations, thereby enhancing the model’s sensitivity to extreme-value dynamics. The primary objective is to improve predictive accuracy during market stress, particularly under warning (20 ≤ VIX ≤ 30) and shock (VIX 30) regimes where conventional models often fail. Using 35 years of historical VIX data (1990–2024), the framework is benchmarked against GARCH (1,1) and a standard Transformer under distinct volatility regimes. Empirical findings show that the proposed model consistently outperforms alternatives: during warning regimes, prediction error is reduced by over 40% relative to both benchmarks, while in shock regimes, improvements exceed 50%, with performance gains validated by Diebold–Mariano tests at the 1% significance level. These results demonstrate both statistical and practical significance, offering risk managers and investors more reliable forecasts during periods of heightened market instability. The contribution of this research lies in providing not only empirical evidence of improved predictive performance but also a generalizable framework for integrating probabilistic indicators into deep learning architectures. The novelty is in showing that probabilistic weighting of attention can transform standard neural architectures into early-warning systems capable of capturing regime shifts in financial markets. Beyond VIX forecasting, this methodological contribution has broader applicability to equities, exchange rates, and commodities, where identifying and responding to volatility shocks is critical for risk management and investment decision-making.